LEVEL UP AND TUNE IN: ENGAGING YOUNG LEARNERS THROUGH VOCABULARY SONGS AND INTERACTIVE GAMES - Maghfiroh, Fitriatul; Widiyanti, Kris (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2026)
This community service study investigates the challenges of low student participation, limited vocabulary mastery, and lack of confidence among learners at Safira English Course in Situbondo. Preliminary observations indicate that conventional instructional practices, primarily based on memorization and repetitive exercises, have not effectively fostered communicative competence or active engagement. To address these issues, an innovative pedagogical intervention integrating vocabulary songs and game-based learning was implemented. The program was conducted through systematic stages, including needs analysis, instructional design, classroom implementation, and continuous evaluation over two weeks. The intervention combined auditory and kinesthetic learning through song-based repetition and interactive activities such as Fastest Finger and Snake Word. The findings reveal a marked improvement in students’ engagement, vocabulary retention, and speaking confidence. Learners demonstrated increased participation, better recall of lexical items, and greater willingness to communicate in English. These results suggest that multimodal and student-centered approaches significantly enhance the effectiveness of English language instruction. It is concluded that the integration of songs and educational games provides a sustainable and impactful strategy for improving learning outcomes in non-formal EFL contexts